(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2015)
In the wake of the prevalence of constitutionally defined values in the interpretation of the legal system, in view of the inefficiency of a merely legalistic approach, and considering the serious violations of human rights committed during the Second World War, the overriding principle of the dignity of the human person emerged. Considering the value of the human being in itself, there has been a change of perspective, including with regard to civil liability: from punishing the agent who commits an unlawful act to compensating the victim who suffers unjust damage. The fact is that the punitive nature of reparation for the agent who acts in breach of the duty of care and the assessment of the illicit and culpable nature of the conduct for civil liability are placed on a secondary level when confronted with the need for reparation for damage suffered by a person who did not cause it. In this context, the objectification and collectivization of civil liability developed, with the subsequent recognition of objective civil liability and compensation for moral damage, including by ricochet. However, these institutes did not prove sufficient to solve all the complexity of social relations as they were presented in the course of the 20th century. Thus, French jurisprudence, especially the Court of Cassation, from the 1930s onwards, began to recognize the "réparation d’une perte d’une chance", commonly translated into Portuguese as civil liability for the loss of a chance.